Animal models of chronic kidney disease - the missing piece of the puzzle for the development of new therapeutic options - Ilić, Miloš; Stanić, Dušanka; Kravljača, Milica; Petrović, Jelena; Ivanović, Ana; Nedeljković, Jelena; Nikolašević Stojković, Gorana; Pešić, Vesna (Archives of Pharmacy, 2025)
Chronic kidney disease (CKD) is considered one of the most important public health problems today. CKD is characterized by changes in kidney structure and impaired kidney function (reduced estimated glomerular filtration rate). Data show that more than 13% of the population suffers from CKD and that it will be the fifth leading cause of death by 2040. To date, numerous animal models for CKD have been developed. They are used to unravel the pathophysiological mechanisms of CKD development and represent a very important platform for the development of new therapeutic strategies. All animal models for CKD can be systematized in different ways, such as surgical/non-surgical models, subdivisions based on pathological changes in kidney structure or as subdivisions based on the pathophysiological mechanisms leading to the development of CKD. In surgical models, part of the kidney tissue is usually removed, while in non-surgical models, certain substances with nephrotoxic effects are used. The choice of model depends on the experimental design and the aim of the specific study. This paper provides an overview of all currently known animal models for CKD.
Keywords: chronic kidney disease; animal models; nephrotoxicity; pathophysiology; rodents